Unlocking trust in luxury : examining the role of supply chain transparency & sustainability and luxury accessibility - Ramalho, Beatriz Jorge de Vasconcelos (2024)
This study investigates the impact of supply chain transparency and sustainability on brand trust within the luxury industry, focusing on the moderating effect of two distinct luxury product levels: accessible and inaccessible. With the rise in consumer demand for ethical and sustainable business practices, particularly from Millennials and Generation Z, luxury brands face growing pressure to improve transparency and sustainability in their supply chains. Although existing literature emphasizes the importance of such supply chain practices in building brand trust, this study addresses a gap by examining their influence in the luxury sector. Through the distribution of an online survey and quantitative data analysis, this research finds that fostering brand trust in the luxury context is not significantly determined by either supply chain transparency or sustainability. Furthermore, whereas brand trust is higher for accessible luxury products than inaccessible ones, the relationship between supply chain practices and brand trust is not significantly moderated by the luxury level. These findings challenge the current literature, suggesting that in the luxury sector, other factors may be more critical for the cultivation of brand trust, such as brand prestige and heritage. This work9s findings carry interesting insights for luxury brand managers, implying that despite supply chain transparency and sustainability remaining valuable for corporate social responsibility and regulatory compliance, they may not be the main drivers of trust for luxury brands. Further investigation is required to understand how supply chain practices and luxury segmentation can, with other factors, regulate luxury brand trust.